(untitled) (Academia Science Repository, 2023)
303 patients with various clinical forms of acute paraproctitis were treated. All observed patients underwent radical surgery. Therapeutic 52 the tactics and choice of surgical treatment in patients with various clinical forms of acute paraproctitis depend on the localization of the abscess, the location of the primary purulent passage in relation to the fibers of the anal sphincter, the degree of development of the cicatricial process in the pararectal tissue, the rectal wall. The developed complex of tactical and therapeutic measures allows to reduce the length of the patient’s stay in the hospital, significantly reduce the percentage of relapses of the disease, and improve the functional results of treatment.